DNA sequence allignment accelerator using MATLAB / Noraminah Ismail - Ismail, Noraminah (2014)
This paper presents the development of DNA sequence alignment accelerator using MATLAB. The Smith Waterman algorithm has been developed and simulated for nucleotide sequence alignment in optimizing accelerating speed. The development of computational method become the key factor in biomedical engineering and application as the rate of the biological sequence databases has exponentially growth thus increasing the complexity of the DNA sequences. The software development has been run in Intel Core i5 Processor 2.40GHz with 64 bit operating system. Comparison between random and generated sequences alignment has been made. The accelerated run time taken from random sequence alignment over generated sequence average of 50.12% faster than generated sequences.